Early recruiting in NCAA sport: An exploratory study of scarcity effects. Issue 3 (1st September 2020) - Flaherty, Meredith; Sagas, Michael
ABSTRACT: Current sources of information regarding the effects of early recruiting in college athletics, on which recent NCAA bylaw changes were predicated, are grounded in anecdotal accounts of deleterious effects on the psychosocial health of adolescent athletes [e.g. DaSilva, M. (2016, May 17). Straight talk: A special LM roundtable on early recruiting. US Psychological Foundations of AttitudesLacrosse Magazine . http://laxmagazine.com/mag/2016/05/051716_straight_talk_lacrosse_magazine_roundtable_on_early_recruiting.; Popper, N. (2014, January 26). Committing to lay for a College, then Starting the 9th Grade. New York Times . http://www.nytimes.com/2014/01/27/sports/committing-to-play-for-a-college-then-starting-9th-grade.html?_r=0 .). Through the lens of scarcity effects [Brock, T. C. (1968). Implications of commodity theory for value change., 1, 243–275. https://doi.org/10.1016/B978-1-4832-3071-9.50016-7], an exploratory study was conducted to examine parents' perspectives on the effects of an accelerated recruiting timeline on the college choice factors, the decision to accept a verbal scholarship offer, and the psychosocial outcomes of the recruiting process for their child. Interviews ( N =12) conducted with parents of female soccer prospective student-athletes who were recruited prior to NCAA permissible contact windows indicated that brand value and program coach were given primacy over academics as college choice factors, and that the fear of losing out on a scholarship and the desire for cognitive closure affected the timeline for accepting a verbal scholarship offer.